Mechanism Study of Cadmium(Ⅱ) Adsorption on Thiol-Modified Montmorillonite - ZHU Xia-ping; LIU Hui; TAN Jun; LIU Wen-hua; FENG Chao (Yankuang ceshi, 2013)
Montmorillonite (MMT) is a good sorbent of cadmium, but the adsorbability is weak. Thiol-Modified Montmorillonite could increase the adsorption of cadmium, but the studies about thiol-modified montmorillonite (MMT-SH) and the adsorption mechanism of cadmium on MMT-SH are rarely reported. In this study, the MMT-SH was prepared through modifying natural MMT with 3-mercapto-propyl-trimethoxysilane and the adsorption mechanism of cadmium on MMT-SH was investigated. The characteristic results of FT-IR and XRD indicated the successful tethering of the thiol group on MMT. The experimental results of cadmium adsorption on MMT-SH showed that the adsorption efficiency of cadmium on MMT-SH was much better than that on natural MMT, which had been increased 39 times. Adsorption efficiency was influenced by ionic strength and pH value of the system. Except for electrostatic adsorption, ion-exchange and hydroxyl coordination, the thiol coordination was one of the main reactions in adsorption of cadmium on MMT-SH. The adsorption behavior of cadmium on MMT-SH fitted well with the Langmuir adsorption isotherm and Lagergren-second-order kinetic model which indicates that the adsorption is a chemical process. The thermodynamic parameters (ΔH, ΔGandΔS) show that the adsorption of cadmium on MMT-SH is a spontaneous endothermic process.